STUDI PENELUSURAN LULUSAN S1 KEPENDIDIKAN FAKULTAS TEKNIK UNIVERSITAS NEGERI YOGYAKARTA - Thomas Sukardi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2011)
ABSTRACTThis research aim at revealing: (1) graduate absorption from bachelor of education Faculty of Engineering, Yogyakarta State University (YSU) in job market, (2) information of suitability of competence and job oppportunity, (3) feedback from graduates’ employer/ user, (4) opinion form the alumnae. This study can be catagorized as survey research which was conducted in September till November 2010. The research population was the graduates from the year of 2006 to 2012 and this study employed snowball technique as data collection technique. The instrument of data collection were using open and closed questionnaire with online or offline process. The online procedure was through website of http://ft.uny.ac.id/tracer, email of tracerftuny@gmail.com while the offline one was through sending letter. The qualitative data were analyzed by crosstab and percentage and the qualitative one was using categorial analysis. The findings showed that (1) the graduates’absorption can be catagorized as good catagory, the waiting period for the graduates to get a job was less than 3 months with percentage of 52.8%, for period of 3-6 months was 23.1%, more than 12 months was 7.2% and not giving answer was 5.6%; (2) the students’ competence also catagorized as good catagory, but for supporting aspects such as managerial and leadership aspect still needed to be improved; (3) the feedback from graduates’ employers or users were in case of improving managerial ability, leadership aspect, foreign language competence, information technology skills, and soft skills (4) the suggestions from alumnae or the graduates of Faculty of Engineering YSU in order to develop graduates competence on education field were the separation between students community service and teaching practicum though it took in the same location of school, enhancing the guidence process with the lecturers such for scientific writing, enhancing the experience of teaching on the real context especially for the students with educational background, enhancing learning based multimedia, developing the curriculum which was suited with Vocational High School, and the teaching methodology also needed to be reviewed and improved.Keywords: bachelor of education, graduates absorption and graduates’tracer study